The Relationship of Spirituality and Maintaining Health in Intermediate Adulthood: A Theological and Practical Review - Sem Yogie Putra Limiyano; Doni Hasugian; Jonathan Nathanael; Ruddy Karundeng; Titin Suhartini (Asian Journal of Community Services, 2026)
Middle adulthood is a stage marked by physical decline and a higher risk of chronic diseases, making health maintenance essential. From a Christian perspective, caring for physical health is also an act of stewardship before God. This community service activity was conducted as an online seminar for adults aged 40–60 years. The program combined a literature review on health, theological reflection on biblical passages, and seminar-style interviews. Results showed that participants gained a better understanding of the importance of physical health and practical strategies, including regular exercise, healthy eating, and adequate rest. They also recognized the body as the temple of the Holy Spirit, understanding physical health as an integral part of holistic Christian living and honoring God.